An Analytical Study on Global Automotive Price Trends and Influencing Factors - Han, Feiran (Transactions on Economics, Business and Management Research, 2024)
This study analyzes global automotive price trends and the key factors influencing these trends from 2018 to 2023. Using a mixed-method approach, it examines historical data, market conditions, and future projections. The findings highlight the impact of technological advancements, economic conditions, government policies, and changing consumer preferences on automotive prices. The study reveals a consistent increase in electric vehicle (EV) adoption, driven by government incentives and environmental awareness, alongside rising new car prices influenced by higher production costs and advanced features. Inflation and raw material costs have significantly impacted vehicle prices, while government subsidies have facilitated the broader acceptance of EVs. The results underscore the importance of understanding these dynamics for stakeholders to navigate the automotive market effectively. Future research should explore the long-term effects of emerging technologies and evolving regulations on automotive prices. Insights from this study are useful for manufacturers, policymakers, and consumers to make informed decisions in a rapidly evolving industry.